Unveiling the complexity of early childhood caries: Candida albicans and Streptococcus mutans cooperative strategies in carbohydrate metabolism and virulence - Pingping Jin; Lu Wang; Daozhen Chen; Yu Chen (Journal of Oral Microbiology)
Objective To explore the mechanisms underlying the virulence changes in early childhood caries (ECC) caused by Candida albicans (C. albicans) and Streptococcus mutans (S. mutans), with a focus on carbohydrate metabolism and environmental acidification.Methods A review of literature was conducted to understand the symbiotic relationship between C. albicans and S. mutans, and their role in the pathogenesis of ECC. The review also examined how their interactions influence carbohydrate metabolism and environmental acidification in the oral cavity.Results C. albicans and S. mutans play crucial roles in the onset and progression of ECC. C. albicans promotes the adhesion and accumulation of S. mutans, while S. mutans creates an environment favorable for the growth of C. albicans. Their interactions, especially through carbohydrate metabolism, strengthen their pathogenic potential. The review highlights the importance of understanding these mechanisms for the development of effective management and treatment protocols for ECC.Conclusion The symbiotic relationship between C. albicans and S. mutans, and their interactions through carbohydrate metabolism and environmental acidification, are key factors in the pathogenesis of ECC. A comprehensive understanding of these mechanisms is crucial for developing effective strategies to manage and treat ECC.